Genetic dissection of plant height in spring wheat from Pakistan using genome-wide SNPs and allele-specific Rht markers - Suleman, Hafiz Muhammad; Qayyum, Humaira; ur Rehman, Sana; Majeed, Khawar; Mukhtar, Misbah; Zulfiqar, Saima; Mahmood, Zahid; Aziz, Abdul; Fayyaz, Muhammad; Mehvish, Ambreen; Cao, Shuanghe; Rasheed, Awais; et al. (Springer, 2025)
Plant architecture and yield potential of wheat are significantly influenced by plant height (PH). In the present study, a diversity panel consisting of 199 Pakistani wheat cultivars was evaluated for PH in three environments, and a genome-wide association study (GWAS) was conducted to identify loci associated with reduced height. GWAS identified 19 loci associated with reduced height, of which 12 were consistently identified in all environments. Allelic variations were analyzed in the diversity panel for five Rht genes, including Rht-B1, Rht-D1, Rht13, Rht25, and Rht26, using diagnostic KASP markers. Furthermore, a KASP marker was developed to identify the dwarfing allele Rht-B1p in wheat. The GA-insensitive dwarfing allele Rht-B1b allelic frequency was pre-dominant (69.6%), followed by the GA-sensitive Rht26 mutant allele (58.5%). Five dwarfing alleles of Rht25, including Rht25c, Rht25d, and Rht25e were rarely present in the cultivars, with frequencies of 1.5%, 1%, and 0.5%, respectively. The use of alternate dwarfing alleles to reduce PH can increase the genetic base of wheat cultivars by reducing selection pressure on the Rht-B1b/Rht-D1b haplotype and can lead to the development of wheat cultivars with improved characteristics such as reduced lodging risk, increased resource allocation to grain, improved harvest efficiency, enhanced crop stability, and adaptability.